Critical Synthesis Package: Parent's Perceptions of Primary Care (P3C) - Julie K. Zadinsky (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education and research for the Parent's Perceptions of Primary Care (P3C), and (2) a copy of the P3C instrument developed by Michael Seid, PhD. The P3C is a 23-item measure of parents' reported experiences with the quality of their children's primary care as defined by the Institute of Medicine. It includes six subscales measuring Access, Communication, Comprehension, Contextual Knowledge, Coordination of Care, and Longitudinal Continuity. Studies have demonstrated evidence of strong validity, reliability, and feasibility for the P3C total scale, which is short and can be self-administered. Further evaluation of the use of the subscales in the Latino population is needed. English, Spanish, Tagalog, Vietnamese and French versions of the P3C have been used in samples of parents whose providers are practicing physicians and/or residents. In addition, a resident version of the P3C has been developed and used with a national sample of pediatric resident continuity practices. The internal consistency of the resident version of the P3C is similar to the original version, except for the access subscale. Further research is needed to evaluate the psychometric properties of this resident scale. Further, research is needed to evaluate the measurement of changes in the quality of care in pediatric resident practices over time, to evaluate use of the P3C when parents are asked to report on a specific provider, and to evaluate applicability of the P3C to family practice residents and primary care nurse practitioner students.